2019
DOI: 10.1590/1980-5918.032.ao32
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of passive cycloergometry on the cardiovascular system and respiratory mechanics of critically ill patients: a randomized controlled trial

Abstract: Introduction: The rehabilitation of critical patients usually occurs in the bed and is classified as low cardiovascular intensity. Therefore, it is essential to understand the physiological effects of these resources that we apply in clinical practice. Objective: Evaluate the acute effect of passive cycloergometry of lower limbs on respiratory mechanics and cardiovascular parameters in critically ill patients. Method: This was a labeled, randomized, controlled trial conducted in two intensive care units in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
3
0
4
Order By: Relevance
“…These findings were confirmed by Ahmed (2019) who reported that no statistically significant changes between the early ambulation and hospital care groups concerning their health profile data. Some studies reported similar findings (Azarfarin, Totonchi, Arizavi, & Yousefi-Moghadam, 2015; Santos et al, 2019;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…These findings were confirmed by Ahmed (2019) who reported that no statistically significant changes between the early ambulation and hospital care groups concerning their health profile data. Some studies reported similar findings (Azarfarin, Totonchi, Arizavi, & Yousefi-Moghadam, 2015; Santos et al, 2019;Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…A pontuação média foi 6,10 (Desvio Padrão, 1,04) de um total de 10 pontos. Com exceção de dois artigos 6,12 , os escores foram extraídos diretamente da base de dados PEDro (Tabela 3). Os critérios menos atendidos foram os itens: 3 (alocação oculta dos sujeitos), 5 (sujeitos cegos), 6 (terapeuta cego), 7 (acompanhamento adequado) e 8 (análise por intenção de tratar).…”
Section: Scielounclassified
“…Quando procurou-se demonstrar a resposta cardiorrespiratória fisiológica e do débito cardíaco ao exercício, seus autores demonstraram que nenhum músculo ou efeitos sistêmicos foram induzidos pelas técnicas passivas e apenas o exercício em cicloergômetro associado com a EENM aumentou o débito cardíaco e a resposta cardiorrespiratória fisiológica com indução do consumo muscular de oxigênio e aumento do metabolismo muscular 17 . Seus efeitos sobre as alterações da mecânica respiratória e parâmetros cardiovasculares não foram significativos e induz um baixo nível de trabalho muscular 6 .…”
Section: Exercício Em Cicloergômetrounclassified
See 2 more Smart Citations